1996
DOI: 10.1016/s0969-2126(96)00113-x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of UDP-N-acetylglucosamine enolpyruvyltransferase, the target of the antibiotic fosfomycin

Abstract: The present structure reflects the open conformation of the enzyme which is probably stabilized through two residues, a lysine and an arginine, located in the cleft between the domains. Binding of the negatively charged UDPGlcNAc to these residues could neutralize the repulsive force between the two domains, thereby allowing the movement of a catalytically active cysteine residue towards the cleft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
99
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 30 publications
5
99
0
1
Order By: Relevance
“…They concluded that PEP inside the catalytic center was protonated and the enzyme stabilized an oxacarbenium ion upon binding with UDP-GicNAc. The substrate-induced conformational change was later demonstrated in both crystal structure (7,25,26) and fluorescence experiments (21).…”
Section: Evidence Of Oxacarbenium Ion In Addition Stepsmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that PEP inside the catalytic center was protonated and the enzyme stabilized an oxacarbenium ion upon binding with UDP-GicNAc. The substrate-induced conformational change was later demonstrated in both crystal structure (7,25,26) and fluorescence experiments (21).…”
Section: Evidence Of Oxacarbenium Ion In Addition Stepsmentioning
confidence: 99%
“…The reaction mechanisms of both MurA and AroA have been studied intensively with pre-steady state experiments (11,14,15), site directed mutagenesis (11), substrate analogues (16)(17)(18), x-ray crystallography (7,19,20), fluorescence titration (21) and NMR experiments (6,22). Their mechanisms are similar in several aspects.…”
Section: General Acid Base Catalysis and Tetrahedral Intermediatementioning
confidence: 99%
See 1 more Smart Citation
“…However, the discovery that Cys-115 could be replaced by an aspartate without loss of activity (a mutation found in some bacteria including Mycobacteria) led to the conclusion that Cys-115 functions as a general acid-base catalyst and not as a nucleophile in the reaction with PEP (10). Cys-115 is a member of a 10-residue loop in the N-terminal globular domain that undergoes drastic conformational changes upon binding of UNAG by approaching the interdomain cleft and positioning the Cys-115 side chain into the PEP binding site (11)(12)(13)(14)(15). Cys-115 has received considerable attention as the target of covalent modification by fosfomycin (12) and other electrophilic natural products such as terreic acid (16) and cnicin (17).…”
mentioning
confidence: 99%
“…A enzima MurA catalisa o primeiro passo na biossíntese do heteropolímero peptideoglicano, o principal elemento estrutural formador da parede celular das bactérias. [2][3][4] No processo catalisado pela MurA, ocorre a reação entre o UDP-Nacetilglicosamina (UNAG) e o fosfoenolpiruvato (PEP), formando os produtos enolpiruvil-UDP-N-acetilglicosamina (EP-UNAG) e fosfato inorgânico. 2 A enzima AroA catalisa a sexta etapa da biossíntese do corismato, que é um precursor para a biossíntese de compostos aromáticos em plantas, fungos, bactérias e algas.…”
Section: Introductionunclassified